965 Social determinants and gender differences in work-life conflict: the effects of age and marriage. (24th April 2018) - Sahan, Ceyda; Demiral, Yucel
Abstract : Introduction: Work–life conflict (WLC) is defined as '…a form of inter-role conflict in which work and family demands are mutually incompatible, meeting demands of both the domains is difficult' and has become a new topic of research interest. The aim of the study was evaluating social determinants and gender differences in WLC. Methods: The study has been carried out in three workplaces (Call centre, plastic and metal industry) in 807 workers between 01.08.2016 and 01.01.2017. Independent variables were age, gender, maritual status, educational status and occupational class. Dependent variable was WLC. Copenhagen Psychosocial Questionnaire-3 were used to evaluate work life conflict. We analysed the association between social determinants and work life conflict by using chi-square test and logistic regression. Results: Mean age of men and women were 32.1±7.4, 27.2±6.6, respectively. 43.0% were women. WLC was found higher in women (55.9%) than men (42.4%) (p<0.001). White collar, younger and high educated workers had higher risk of having WLC than their reference groups (p<0.05 for all comparisons). Logistic regression analysis revealed that, being younger and married were independently associated with WLC (p<0.05) in women. Being younger was independently associated with WLC (p<0.05) in men. There were no association between educational status or occupational class and WLC in both gender. Conclusion: In this study, an inverse relationship was found between age of the employees and WLC. Marital status is important factor in women but not men in terms of WLC.